A case report on mycotic aneurysm by non-typhoidal Salmonella - Kumar, B. Vijay; Rao, G. Vamshi Nandan; Rao, K. Shivaram; Veena, M. (International Journal of Research in Medical Sciences, 2025)
Non-typhoidal Salmonella (NTS) causing an aortic aneurysm is a rare and serious condition referred as mycotic aneurysm or infected aneurysm. The condition arises with the penetration of Salmonella into aortic wall leading to inflammation, structural compromise and the risk of dilation or rupture of the arterial wall. Due to the considerable morbidity and mortality linked with this condition, prompt diagnosis and vigorous treatment is crucial. This report outlines the case of a 67-year-old male with several comorbidities presented with intense lower back pain and fever. Blood cultures confirmed the presence of Gram-negative bacilli, specifically non-typhoidal Salmonella. Magnetic resonance imaging (MRI) showed infrarenal abdominal aortic aneurysm and computed tomography (CT) depicted multilobulated saccular aneurysm originating from the anterior wall of the infrarenal abdominal aorta, accompanied by a large peripheral hypodense thrombus. The patient successfully underwent endo-vascular aortic aneurysm repair (EVAR) along with antibiotic therapy. The combination of timely surgical intervention and extended antibiotic treatment resulted in excellent outcomes for the patient.